Maximization of natural gas liquids production from an - Ahmed Abd El-Kader Bhran; Mohamed Hassan Hassanean; Mohamed Galal Helal (Egyptian Journal of Petroleum)
It is known that the price of liquefied petroleum gas (LPG) is higher than that of natural gas from which it is derived. So the modification of a natural gas plant to produce LPG instead of lighter hydrocarbon gases is very important in the view point of economics. The aim of the present work is directed to the modification of Salam gas plant (Khalda Petroleum Company-Egypt) to produce LPG from the NGL instead of producing hydrocarbon gases during the NGL stabilization. This can be achieved after adding de-ethanizer and de-butanizer towers. The simulation tool used in this study is HYSYS version 8.4. The produced LPG of 100 ton/day can participate to solve the LPG shortage problem in Egypt and provide a national service to the people of Matruh Governorate. The economic study based on the economic analyzer of HYSIS showed that the pay-back period of the added two towers and their additional equipment has a high investment strength which means that all modification costs will be recovered within a short time. Furthermore, there are other benefits from this modification. The simulation results showed that there is a capacity saving of 56 tons/day in the export pipeline which transfers the gases to western desert gas complex (WDGC) at Alexandria. In the same manner, the modified plant provides a capacity saving of 88 tons/day in the dehydration unit and reduces horse power consumption in recycle and first stage export compressors. This modification can be taken as guidelines for both new and plants in operation to increase their profits.